The Analysis of Bu Tejo’s Language in Short Movie “Tilik” - Chistina Christina (Metaphor, 2020)
Movies are at times reflections of the society in which the story takes place. “Tilik” is one of the short movies that has gone viral lately due to the somewhat controversial yet common theme it raises: common housewives’ talk. The talk the movie presents is the so-called gossip surrounding a young beautiful village dream female named Dian, whose job and personality were deemed as murky. This study aims to explore the language used by one of the main characters in the movie, bu Tejo, whose expressions are highly influencing in the movie, in terms of the speech acts she performed. Her appearance has ignited lively discussions in society. It is descriptive in nature and carried out by the observation method. The result reveals that her speech acts are mostly in the form of representatives. She was also seen to produce directives, commissives, and expressives whose number are in line respectively. Her speech acts are for the most part direct, in which the functions are similar to the structure of her utterances.